1976
DOI: 10.1002/dev.420090312
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prenatal and postnatal protein malnutrition on physical and motor development of the rat

Abstract: The effects of protein malnutrition in the early stages of mammalian life have been found to be pervasive and frequently very persistent. We conducted this experiment to investigate the relative effects of protein deficiency during prenatal and/or postnatal (preweaning) stages of development in order to evaluate the effects of the timing of protein malnutrition and its duration and found significant deficits on a variety of measures of physical and motor development. Animals maintained on low protein diets bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…natal malnutrition affected growth of mice, prenatal malnutri-Psychologists have reported a number of effects of malnutrition experienced by infant laboratory rats and mice on the subsequent reproduction (Sykes and Cheyne 1976;Huck et al 1986), reflexes (Smart and Dobbing 197 I), problem-solving ability (Bush and Leathwood 1975), and social behaviour (Frankovi 1973;Randt et al 1975;Whatson et al 1976) of well-nourished adults. Ecologists, however, have generally not considered the long-term effects of infant malnutrition on populations (but see Andreassen and Ims 1990;and Mech et al 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…natal malnutrition affected growth of mice, prenatal malnutri-Psychologists have reported a number of effects of malnutrition experienced by infant laboratory rats and mice on the subsequent reproduction (Sykes and Cheyne 1976;Huck et al 1986), reflexes (Smart and Dobbing 197 I), problem-solving ability (Bush and Leathwood 1975), and social behaviour (Frankovi 1973;Randt et al 1975;Whatson et al 1976) of well-nourished adults. Ecologists, however, have generally not considered the long-term effects of infant malnutrition on populations (but see Andreassen and Ims 1990;and Mech et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Low-protein diets administered prenatally (Bush and Leathwood 1975;Schenck et al 1978) and during the suckling period cause severe and permanent impairment of growth in rats and mice (Smart and Dobbing 197 1 ;Letvisky and Barnes 1972;Stewart et al 1975;Sykes and Cheyne 1976;Whatson et al 1976;Whatson and Smart 1978;Martin et al 1987). In white mice, postweaning malnutrition followed by adequate nutrition results in an almost complete catch-up in weight (Bush and Leathwood 1975;McKiggan 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Our study indicated a positive relationship between dietary protein levels and activity. Similarly, protein-restriction reduced activity and exploratory behavior in mice and rat pups (Frankova, 1973;Frankova & Barnes, 1968;Pillay et al, 2016;Sykes & Cheyne, 1976;Watkins et al, 2008). In contrast, rats fed high protein diets for prolonged periods exhibit hyperactivity (Onaivi, Brock, & Prasad, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Head tremors have been reported in rat pups of food-restricted females (Simonson, Sherwin, Anilane, Yu, & Chow, 1969). Maternal undernutrition has also been shown to affect the development of specific reflexes and locomotor patterns in the young rat (Altman et al, 1970;Smart & Dobbing, 1971;Sykes & Cheyne, 1976) and cat (Simonson, 1979). Thus, impaired locomotor abilities may have been partially responsible for the delay observed in the development of home-orientation behavior in our restricted kittens.…”
Section: Discussionmentioning
confidence: 99%